How and Why Practitioners Think and Work Politically - Evidence from C hemonics Programming Across Sectors - Kantelberg, Renee; Swift-Morgan, Jennifer; Watson, Bryce (Chemonics International, 2022)
Most development practitioners have long recognized that deep contextu al knowledge is crucial to understanding how projects interact with th eir local systems and, in turn, to navigating these systems. Moreover, this knowledge must complement projects' technical solutions, or they will fall flat and may even undercut project objectives as they clatt er down. What, then, explains practitioners' particular interest in TW P as an explicit strategy and more than just "doing good development"? This report responds to that question and to the many calls for a mor e comprehensive picture of TWP by presenting new evidence of the vario us forms that TWP may take in practice. The evidence comes from a 2022 study that Chemonics undertook to foster more robust learning about T WP. Specifically, we closely examined Chemonics implemented projects t hat used or are using various forms of TWP in nine countries: Banglade sh, Iraq, Mozambique, the Philippines, Pakistan, Syria, Timor-Leste, a nd Tunisia. In conducting the study, we interviewed multiple staff fro m these projects. We complemented what we learned from these projects with a review of eight additional Chemonics- implemented projects appl ying TWP that had received dedicated support from Chemonics’ Center fo r Politically Informed Programming (the Center). We consider these fin dings alongside those of the recent (2022) USAID-Chemonics study on po litical economy analysis (PEA) usage to identify and articulate what i s different and more effective about PEA processes and TWP practices t hat have received more support.